Peranan Manajemen Pengetahuan dalam Peningkatan Kompetensi dan Kinerja Pimpinan Militer - Andrey Satwika Yogaswara; Disman M.S; Eeng Ahman; Fitriani Reyta (Masoem University, 2022)
The Army Military Police has the task of carrying out policies and carrying out the functions of the Military Police to support the implementation of the basic tasks of the Army. In creating value and producing competitive advantage or excellent performance within the Army Military Police, knowledge management is needed to meet the standards of the Army Leadership competencies in improving performance. In the past two years, the performance of the Military Police was considered to be unsuccessful, as seen from the rise of violations in the Indonesian Army. In this study, the population and sample were as many as 74 people who were leaders of the Military Police in Indonesia. The test was carried out using a partial least square approach, the results of the study indicated competence did not directly affect the performance of the leadership, the moderating variable required for knowledge management in improving the performance of the military police leadership.